Epidemiology and genetic characteristics of coxsackievirus A16 associated with hand-foot-mouth disease in Hangzhou city, Zhejiang province from 2021 to 2024 - Xu, Qihao; Qiu, Xiaofeng; Yu, Yue; Wen, Yanping; Zhang, Guozhong; Li, Jun (Frontiers in Microbiology, 2025)
Hand-foot-mouth disease (HFMD) is a common acute infectious disease in children caused by various enteroviruses (EV). CV-A16 is one of the main pathogens of HFMD, leading to multiple outbreaks of HFMD worldwide, especially in the Asia-Pacific region. This study aims to investigate the molecular epidemiological characteristics of the coxsackievirus A16 (CV-A16) that cause HFMD in Hangzhou, Zhejiang Province from 2021 to 2024. A total of 2,105-laboratory diagnosis HFMD cases were collected, of which 529 were CV-A16 positive samples. The detected number of CV-A16 began to rise in March, peaked in May–August, and then decreased in September. Its distribution was highest in children aged 1–5 years, with more males than females. The phylogenetic analysis indicated that the B1a and B1b subgenotypes were simultaneously prevalent in Hangzhou from 2021 to 2023. The B1c evolutionary branch detected in Hangzhou in 2023 experienced a sudden increase in quantity in 2024, with the same proportion as B1a, suggesting a change in the subgenotype prevalence of CV-A16 virus. Evolutionary analysis also confirmed that the CV-A16 in Hangzhou is genetically stable and the B1a lineage emerged earlier, followed by B1b, while B1c is a newly emerging lineage. There were three specific amino acid variations (P3S, I235V, and T240A) in the VP1 sequence of B1c. These findings have expanded the global genetic resources of CVA16 and provided supporting evidence for the prevention and control of HFMD. Meanwhile, the CV-A16 B1c outbreak branch that emerged in Hangzhou from 2023 to 2024 also highlights the necessity of strengthening the monitoring of virus evolution and epidemiological dynamics in this region.